Number of repetitions and muscle fatigue in system in multiple yers series leg press 45 the thread and direct in heal thy men - Magosso, Rodrigo Ferro (2013)
The objective was to determine number of repetitions and muscle fatigue during training in multiple sets at 45 º Leg Press and Arm Curl. Six men who practice strength training for at least a year, attended the laboratory on 3 occasions, the first to determine the maximum load (1RM) in Leg Press and Arm Curl, and the following two to carryout the training protocol (4 sets at 75% 1RM with 1 minute recovery between each) in multiple sets for each exercise in randomized order and separated by 72h. We observed significant differences in the number of repetitions performed in 4 series of exercises in the Leg Press and Arm Curl respectively: 1º: 14,5 ± 2,3 versus 10,7 ± 1,2 (p = 0,0136), 2º: 10,2 ± 1,8 versus 4,5 ± 1,8 (p = 0,0009), 3º: 7,7 ± 2,0 versus 1,8 ± 1,2 (p = 0,0009), 4º: 7,3 ± 2,1 versus 1,5 ± 0,8 (p = 0,0007). Total volume of repetitions in Leg Press was significantly higher when compared with Arm Curl (39,7 ± 6,3 e 18,5 ± 4,5, respectively; p = 0,0006). Fatigue index in Leg Press was greater and statistically significant compared to Arm Curl (31,6 ± 9,4% e 56,6 ± 6,8%, respectively; p = 0,0004). In conclusion, the results show that the Arm Curl is held low number of repetitions and it has greater fatigue when compared to the Leg Press intensity of 75% 1RM.